Emotional culture of the teacher in the context of vocal-choral installation (Pedagogy of Higher and Secondary Education, 2013)
Furdak T. D. Emotional culture of the teacher in the context of vocal-choral installation.The article analyzes the psychological, pedagogical, musicological literature, classification of most important types of emotions, discussed the importance of the development of emotional culture of the conductor, music teacher, secondary school, in the context of the implementation of vocal-choral installation.
Keywords: emotional culture; choir; teacher; conductor of the function of emotion; vocal-choral setting